The Growth and Failure of U. S. Manufacturing Plants - Dunne, Timothy; Roberts, Mark J.; Samuelson, Larry (Quarterly Journal of Economics, 1989)
This paper examines the patterns of postentry employment growth and failure for over 200,000 plants that entered the U. S. manufacturing sector in the 1967–1977 period. The postentry patterns of growth and failure vary significantly with observable employer characteristics. Plant failure rates decline with size and age as do the growth rates of nonfailing plants. The expected growth rate of a plant, which depends on the net effect of these two forces, declines with size for plants owned by single-plant firms but increases with size for plants owned by multiplant firms.